Managing the blue line: policing the police : how to implement, audit and sustain effective policing standards - Epperson, Chet (Little Creek Press, 2023)
“The public supports the police but sometimes needs help understanding how police chiefs, officers, and departments can make questionable decisions when the stakes are high. Millions of dollars are paid by cities each year to settle police misconduct and risk issues. What is happening to our nation's police departments, and what can communities do about it? In this fast and hard-hitting book, Chief Epperson outlines several steps police agencies can take to improve their responsibilities. At the same time, this book empowers communities and individuals with specific and direct information to manage the blue line.” – Amazon